Improved Interleukin-10 Levels Through 8 Weeks of Moderate Intensity Combination Exercise in Obese Women - Muhammad Rifki Fauzi (Indonesian Conditioning Coaches, 2025)
Obesity is closely associated with chronic low-grade inflammation, which plays an important role in the development of various comorbidities and its prevalence continues to increase year by year. In obese individuals, IL-10 levels tend to be lower which is associated with increased insulin resistance, hyperinsulinemia, and increased risk of metabolic dysfunction, including type 2 diabetes, exacerbated by obstructive sleep apnea, contributing to systemic inflammation and cardiovascular risk. Physical exercise is believed to have beneficial effects on obesity and suppress inflammation followed by a decrease in fat mass and an increase in muscle mass. The aim of this study was to prove that combined aerobic and resistance training with moderate intensity increases anti-inflammatory cytokine production in obese women. This study used a true experimental method with a pretest-posttest control group design. 16 obese women aged between 20 and 30 years were divided into two groups: control group (K1; n=8), and combination exercise group (K2; n=8). The exercise intervention was moderate intensity combination exercise (60%-70% Hrmax; 60-70% 1-RM), with a frequency of 5x/week for 8 weeks. With a detection range of 0.78-50 pg/mL and sensitivity level of 0.49 pg/mL, inflammation levels were measured both at pretest and posttest using ELISA kit method. Data with a significant level (p>0.05) were evaluated with the Paired Samples T-test. The results of the analysis of IL-10 levels between pretest and posttest in K1 (1.74 ± 0.13 vs 1.75 ± 0.19 ng/mL; p = 0.951), and K2 (1.75 ± 0.19 vs 2.41 ± 0.72 ng/mL; p = 0.016). This study showed that obese women had higher levels of IL-10 after 8 weeks of combined exercise.